Regulation of influenza A virus infection by Lnc‐PINK1‐2:5. Issue 8 (24th February 2022) - Pushparaj, Samuel; Zhu, Zhengyu; Huang, Chaoqun; More, Sunil; Liang, Yurong; Lin, Kong; Vaddadi, Kishore; Liu, Lin
Abstract: Influenza virus causes approximately 291, 000 to 646, 000 human deaths worldwide annually. It is also a disease of zoonotic importance, affecting animals such as pigs, horses, and birds. Even though vaccination is being used to prevent influenza virus infection, there are limited options available to treat the disease. Long noncoding RNAs (lncRNAs) are RNA molecules with more than 200 nucleotides that do not translate into proteins. They play important roles in the physiological and pathological processes. In this study, we identified a novel transcript, Lnc‐PINK1‐2:5 that was upregulated by influenza virus. This lncRNA was predominantly located in the nucleus and was not affected by type I interferons. Overexpression of Lnc‐PINK1‐2:5 reduced the influenza viral mRNA and protein levels in cells as well as titres in culture media. Knockdown of Lnc‐PINK1‐2:5 using CRISPR interference enhanced the virus replication. Antiviral activity of Lnc‐PINK1‐2:5 was independent of influenza virus strains. RNA sequencing analysis revealed that Lnc‐PINK1‐2:5 upregulated thioredoxin interacting protein (TXNIP) during influenza virus infection. Overexpression of TXNIP reduced influenza virus infection, suggesting that TXNIP is an antiviral gene. Knockdown of TXNIP abolished the Lnc‐PINK1‐2:5‐mediated increase in influenza virus infection. In conclusion, the newly identified Lnc‐PINK1‐2:5 isoform is an anti‐influenza lncRNA acting through the upregulation of TXNIP gene expression.